How do stimulus-dependent correlations between V1 neurons affect neural coding? - Montani, Fernando (2007)
Nearby neurons in the visual cortex often partially synchronize their spiking activity. Despite the widespread observation of this phenomenon, its importance for visual coding and perception remains to be uncovered. We used information theory to study the coding of the contrast and direction of motion of visual stimuli by pairs of simultaneously recorded neurons in the macaque primary visual cortex. Direction coding showed weak synergistic effects at short timescales, trailing off to informational independence at long timescales. In comparison, contrast coding was dominated by redundancy due to the similarity in contrast tuning curves.